ABOUT ENGINEERING AND GEOLOGICAL SURVEYS OF SOIL PROPERTIES IN THE CONSTRUCTION OF APARTMENT BUILDINGS - Lipatova, Ekaterina; Basik, Daniil; Petrova, Katerina; Makeeva, Ekaterina; Sergeevna Gorelysheva, Natalia; Alecksandrovich Seroshtan, Denis; Viktorovna Goncharova, Elizaveta (Revista Gênero e Interdisciplinaridade, 2020)
Engineering and geological surveys are summative concepts, the essence of which is to conduct a study of the geological properties of the soil on the territory of the construction site. The main goal is to obtain all the necessary materials to fully justify the possibility of designing and building any object on the selected territory. This study describes engineering and geological surveys of soil properties for the preparation of project documentation for the construction of an apartment building at the address Kirov region, Vyatskopolyansky district, village. Krasnaya Polyana, Druzhba str., 1. Statistical processing of physical characteristics of the studied soils, as well as indicators of physical and mechanical properties of soils are presented.